Human Physiology Education through Pedagogy, Andragogy, and Heutagogy to Improve Nursing Practice towards Ensuring Patient Safety - Opoku, Albert; Adjei, Asafo, T. A.; Afriyie-Anto, Jones; Usman, Mustapha Bin (British Journal of Healthcare and Medical Research, 2026)
A strong grasp of human physiology is crucial for safe and effective nursing practice because it facilitates clinical reasoning, decision-making, and timely patient interventions. Traditional teaching methods, however, might not be sufficient to meet the various learning requirements of practicing nurses and nursing students at various phases of their careers. In order to improve patient safety, this study investigates the integration of pedagogy, andragogy, and heutagogy as complementary educational frameworks for teaching physiology in nursing education. Pedagogical approaches use instructor-led instruction and structured guidance to help new learners acquire foundational knowledge. Adult learners can apply physiological concepts to real-world clinical contexts thanks to andragogical strategies that emphasize self-directed, experience-based learning. By encouraging nurses to recognize their own learning needs, reflect on their practice, and participate in ongoing professional development, heutagogical approaches further foster learner autonomy, critical thinking, and adaptability. Nursing educators can promote greater comprehension, clinical competency, and lifelong learning abilities by integrating physiology instruction with these progressive learning paradigms. By strengthening nurses’ physiological knowledge and enhancing their clinical judgment, the integration of these frameworks may help to improve patient safety and care quality by lowering errors.